Genus Zero Complete Maximal Maps and Maxfaces with an Arbitrary Number of Ends - Kumar, Pradip; Mohanty, Sai Rasmi Ranjan (Comptes Rendus. Mathématique)
We prove the existence of a genus-zero complete maximal map with a prescribed singularity set and an arbitrary number of simple and complete ends. We also discuss the conditions under which this maximal map can be made into a complete maxface.